Perceptions and Governance of Emerging Technologies in New Zealand: Preparing the Next Generation for an IT-Driven Future - Alam, Shafiq; Weerasinghe, Kasuni; Pauleen, David; Jafarzadeh, Hamed; Taskin, Nazim; Yu, Ji (AIS Electronic Library (AISeL), 2025)
In the era of Industry 4.0, the world is rapidly evolving with emerging technologies like Artificial Intelligence and the Internet of Things. These technologies bring various benefits to sectors, such as healthcare, education, governance, and transportation, but they also raise concerns about privacy, security, and usability. To maximise the advantages and minimise negative effects, appropriate policies and regulations are crucial. Understanding public perceptions of emerging technologies is vital for their acceptance and effective governance. This research focuses on New Zealand, aiming to comprehend public perceptions through a survey conducted in three stages: literature review, survey instrument development, and empirical data collection. Initial findings from the survey of 450 responses indicate that the public shows moderate support for emerging technologies in New Zealand. However, addressing concerns related to data privacy and accountability is essential. Future work involves testing correlations between knowledge levels and perceptions/concerns, revising the survey instrument, and conducting a nationwide survey with a demographic and ethnicity-based approach to gauge public sentiment.
Keywords: Emerging Technologies; Artificial Intelligence; Facial Recognition; Virtual Reality